2018
DOI: 10.1159/000487311
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Particle Radiotherapy in Various Stages of Hepatocellular Carcinoma: A Pilot Study

Abstract: Aim: We analyzed the effectiveness of external particle radiotherapy (PRT) as an alternative therapy for various stages of hepatocellular carcinoma (HCC). Methods: Eighty-three patients with HCC underwent PRT in our hospital from 2007 to 2015 (proton beam radiation in 58 patients and carbon ion radiation in 25 patients), including patients with early-stage HCC (single HCC measuring ≤3 cm, Barcelona Clinic Liver Cancer [BCLC] stage 0 or A) (group A, n = 30), those with intermediate-stage HCC (HCCs measuring ≥3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Proton therapy for HCC remains a research topic of interest to this day in East Asia. In addition to further retrospective data [ 27 , 28 , 29 , 30 ], prospective evidence was also generated. An early phase II trial included 30 patients with HCC and liver cirrhosis who received 76 GyE of PBT in 20 fractions [ 31 ].…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Proton therapy for HCC remains a research topic of interest to this day in East Asia. In addition to further retrospective data [ 27 , 28 , 29 , 30 ], prospective evidence was also generated. An early phase II trial included 30 patients with HCC and liver cirrhosis who received 76 GyE of PBT in 20 fractions [ 31 ].…”
Section: Clinical Datamentioning
confidence: 99%
“…The analyses in the studies mentioned above found different combinations of variables to be correlated with survival. The risk factors that were consistently shown to be relevant include the Child–Pugh classification [ 26 , 27 , 34 ] and tumor stage [ 28 , 29 , 34 ]. Another factor is the indocyanine-green retention rate at 15 min (ICG R15).…”
Section: Clinical Datamentioning
confidence: 99%
“…Although it requires acceleration with a large cyclotron, C-ion RT is theoretically an ideal radiotherapy technique [16][17][18]. Furthermore, some previous studies have shown that Cion RT could be performed with fewer fractions than proton beams [19,20]. A short treatment duration also has the advantage of maintaining the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%